PENGARUH TERAPI RENDAM AIR HANGAT DAN AIR HANGAT JAHE TERHADAP PENURUNUNAN TEKANAN DARAH PADA PASIEN HIPERTENSI DI PUSKESMAS TELAGA BIRU - Muh. Isman Jusuf; Andi Nuraina Sudirman (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Hipertension or high blood pressure is a health problem that is found in the community.The purpose of this research is to find out whether there is influence of soaiking therapy in warm water and warm water with ginger toward decrease in blood pressure in hypertensive patients. The method used in this research is quasy experimental pre-post test. The technique of sampling with the purposive sampling. The simple in this research was 15 people. Analysis of the test data by using paired sample T-test. The result of statistical tests is obtained that the amount of 0,000 (0,005). Conclusion there is the influence in therapeutic soak of warm water and warm water ginger toward a decrease in blood pressure in hypertensive patient in Telaga biru clinics.